2018
DOI: 10.2147/ndt.s158688
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of parent participation in occupational therapy for children with developmental delay

Abstract: IntroductionThis study aims to explore the impact of Parent Participation Program on the development of developmental delay children.MethodsPretest-posttest equivalent-group experimental design study was used in this paper. A total of 30 pairs of developmental delay children aged 0–72 months and their parents participated into this study. They were divided into two groups, namely control group and experimental group, according to parents’ wishes. The objects of study in control group received 16 courses of dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…One of these principles is to pay attention to the differences in learning styles of different people, which may mean they prefer educational content in the form of written text, video, face-to-face, or practical exercises. Studies conducted on training parents with disabled children and parents with normal school children found parents had preferred different teaching strategies (Darch et al, 2004; Ghashghaee et al, 2016; Hornby and Lafaele, 2011; Lin et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of these principles is to pay attention to the differences in learning styles of different people, which may mean they prefer educational content in the form of written text, video, face-to-face, or practical exercises. Studies conducted on training parents with disabled children and parents with normal school children found parents had preferred different teaching strategies (Darch et al, 2004; Ghashghaee et al, 2016; Hornby and Lafaele, 2011; Lin et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Parents' need to be supported by therapists, especially in early sessions of therapy when parents are often disappointed or confused about the information they receive (Dunn et al, 2012). Therapists' ongoing follow-up can help parents continue using the process they learned outside the therapy setting (Lin et al, 2018). Effective communication supports positive relationship between parents and therapists and is an essential part of a family-centered approach (King et al, 2000a(King et al, , 2000b.…”
Section: Discussionmentioning
confidence: 99%
“…In most therapy sessions the child, therapist and parent collaborated on the activity. Lin, Lin, and Yu (2018) found that children with developmental delays had greater developmental outcomes when their parents were involved in the therapy session than when parents were not present. Parent involvement in therapy has been considered integral to the child's overall engagement in therapy and their occupational performance outcomes (D'Arrigo et al., 2019) and a recommended strategy to enhance child engagement and achievement of therapy goals.…”
Section: Discussionmentioning
confidence: 99%
“…The statistical analyses showed that the intervention led to a significant change in general health score and its subscales in the experiment group at different measurement occasions. Lin et al (2001) found that cognitive-behavioral treatment was significantly effective in the mothers in experiment group and improved their ability to speak, do self-care, and do child care [20]. Cather (2005) reported that cognitive-behavioral approach was effective in the treatment of mental health symptoms [21].…”
Section: Discussionmentioning
confidence: 99%
“…The GHQ-28 covers four subscales viz. physical symptoms (statements 1-7), anxiety and sleep disorders (statements 8-14), social function disorder (statements (15)(16)(17)(18)(19)(20)(21), and severe depression (statements 22-28). The statements are four alternative questions…”
Section: Data Collection and Instrumentsmentioning
confidence: 99%